Men's visual attention to and perceptions of women's dance movements. (October 2016) - Röder, Susanne; Carbon, Claus-Christian; Shackelford, Todd K.; Pisanski, Katarzyna; Weege, Bettina; Fink, Bernhard
Abstract: Sexual selection may have shaped male visual sensitivity to characteristics that provide information about female mate quality. Indeed, men judge certain facial and bodily configurations of women to be attractive, possibly because those configurations signal health and fertility. Most of this evidence derives from the study of women's facial and body photographs. We tested the hypothesis that attractive female dancers receive greater visual attention from men than do unattractive dancers. Twenty-nine men viewed video pairs of pre-categorized high and low attractive female dancers. Their eye gaze was tracked and they also provided ratings of attractiveness, femininity, and dance movement harmony. High attractive dancers received greater visual attention than did low attractive dancers and men's visual attention correlated positively with their judgments of attractiveness, femininity, and dance movement harmony. We discuss our findings in the context of the 'beauty captures the mind of the beholder' hypothesis and the role of dance movements in human mate selection. Highlights: Men's visual attention to female dance movements Men spend higher visual attention to dance movements of attractive female dancers. Men judged attractive dancer higher on femininity and dance movement harmony. Men's visual attention correlates positively with attractiveness assessments.